Nasopharyngeal abscess causing inspiratory dyspnoea in a domestic cat - Annie Slater; Raquel del Solar; Jennifer Raj (Journal of Feline Medicine and Surgery Open Reports, 2023)
Case summary An 11-month-old female domestic shorthair cat presented with a 24 h history of inspiratory dyspnoea, abnormal upper respiratory tract sounds, gagging, retching and making exaggerated swallowing motions. Retroflexed nasopharyngoscopy revealed a large, right-sided nasopharyngeal mass that was seen to exude purulent material and a possible small foreign body when pressure was applied with forceps. Thorough expression of the mass alleviated clinical signs. Cytology revealed septic neutrophilic inflammation, and a Pasteurella species with no noted antimicrobial resistance was cultured. The cat was discharged with oral antibiotics and analgesia and made a full recovery, with no recurrence of clinical signs at the 6-month follow-up. Relevance and novel information Abscess formation in the nasopharyngeal region has not been previously reported in cats, to the authors’ knowledge. The cause of the abscess was suspected to be a foreign body, but other aetiologies could not be fully excluded. This case demonstrates that nasopharyngeal abscesses are a rare but potentially significant differential diagnosis for upper respiratory tract obstruction in cats.